Relationships between personality traits and attitudes toward the sense of smell - Seo, Han-Seok; Lee, Suji; Cho, Sungeun (Frontiers in Psychology, 2013)
Olfactory perception appears to be linked to personality traits. This study aimed to determine whether personality traits influence human attitudes toward sense of smell. Two-hundred participants’ attitudes toward their senses of smell and their personality traits were measured using two self-administered questionnaires: the Importance of Olfaction Questionnaire and the Eysenck Personality Questionnaire-Revised (EPQ-R). Demographics and olfactory function were also assessed using a self-administered questionnaire. Gender-induced differences were present in attitudes toward sense of smell. Women participants were more dependent than men participants on olfactory cues for daily decision-making. In addition, as participants evaluated their own olfactory functions more positively, they relied more on olfactory information in everyday life. To determine a relationship between personality traits and attitudes toward sense of smell, Spearman partial correlation analyses were conducted with controlling the factors that might influence attitudes with respect to sense of smell (i.e., gender and self-awareness of olfactory function) as covariates. Participants who scoring high in lie-scale (i.e., socially desirable and faking good) tended to use olfactory cues both for daily decision-making related to social communication and product purchase. In conclusion, our findings demonstrate a significant association between personality traits and attitudes toward sense of smell.